A large Shiva Linga within the Garbhgriha of the Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Inside the central garbhagriha (sanctum sanctorum) of the central shrine in the Neelkanth Mahadev Temple is a large Shiva linga (aniconic representation of Shiva). It is on a high pedestal. The temple is actively used for worship. The Shivalinga is made up of polished stone.